Strategic Financial Planning and Its Effect on Company Resilience in an Uncertain Market in Indonesia - Judijanto, Loso; SY, Arniwita; Ermaini, Ermaini (Westscience Press, 2025)
This study examines the effect of strategic financial planning on company resilience in an uncertain market environment in Indonesia. Using a quantitative approach, data were collected from 55 companies through a structured questionnaire. Strategic financial planning was assessed through budgeting, forecasting, risk management, and resource allocation, while company resilience was measured by adaptability, sustainability, and financial stability. Data analysis was conducted using SPSS version 25, incorporating descriptive statistics, correlation analysis, and regression analysis. The results indicate a strong positive relationship (r=0.72,p<0.01r = 0.72, p < 0.01r=0.72,p<0.01) between financial planning and resilience. Regression analysis confirmed the significant impact of financial planning (β=0.68,p<0.001β = 0.68, p < 0.001β=0.68,p<0.001), explaining 52% of the variance in resilience. These findings highlight the critical role of financial planning in enabling companies to adapt and thrive in uncertain markets. The study concludes with practical recommendations for enhancing financial planning practices to strengthen resilience.